Knowledge and attitudes of syphilis and syphilis pre-exposure prophylaxis (PrEP) among men who have sex with men in Vancouver, Canada: a qualitative study. Issue 11 (21st November 2019) - Nath, Ronita; Grennan, Troy; Parry, Robin; Baharuddin, Fahmy; Connell, James P; Wong, Jason; Grace, Daniel
Abstract : Objectives: In British Columbia, Canada, syphilis is at record-high rates, with over 80% of cases in 2017 seen in gay, bisexual and other men who have sex with men (GBM). The syphilis epidemic is of particular concern for those living with HIV, since syphilis may lead to more serious complications in this population. We sought to explore syphilis-related knowledge and attitudes around biomedical prevention options for syphilis, with the goal of informing effective strategies to prevent syphilis. Design: We conducted a qualitative study consisting of in-depth, individual interviews from December 2016 to June 2017. Our interviews focused on participants' knowledge about syphilis and perceptions regarding syphilis pre-exposure prophylaxis (PrEP). Interviews were analysed using Grounded Theory. Participants: Twenty-five GBM were interviewed (64% white; median age: 43 years), including men living with HIV and/or with a history of syphilis. Setting: Vancouver, British Columbia. Results: Five interrelated themes emerged. First, GBM were aware of the local syphilis epidemic. Second, syphilis-related knowledge differed according to syphilis and HIV serostatus. Third, competing ideas emerged regarding men's concerns about syphilis. While our participants expressed concern about getting syphilis, they also described the importance of sexual pleasure. Fourth, many participants said that syphilis was not perceived to be alarming; preventing HIV infection remained a primary concern for many. Finally, while syphilis PrEP was appealing to those living with HIV or a prior syphilis diagnosis, others were concerned about antibiotic resistance, cost and side effects. Conclusions: Our participants organised their safer sex strategies around HIV, not syphilis. Although syphilis-related knowledge was relatively high among GBM living with HIV and those with a prior syphilis diagnosis, this knowledge did not appear to be related with safer sexual practices, such as increased condom use. This work highlights the importance of examining other potential prevention solutions, such as syphilis PrEP.